Thrombomodulin Levels during Normal Pregnancy, at Delivery and in the Postpartum: Comparison with Tissue-type Plasminogen Activator and Plasminogen Activator Inhibitor-1 - Moerloose, de P.; Mermillod, N.; Amiral, J.; Reber, G. (Thrombosis and Haemostasis, 1998)
Some studies suggest that soluble thrombomodulin (TM) could be used as a marker of preeclampsia or eclampsia. However little is known about the sequential changes of TM during the course of normal pregnancy.Levels of TM were determined in 100 women with uneventful pregnancies. Samples (n = 394) were divided into five study intervals, three during pregnancy, one at delivery and one three days postpartum.As compared with TM levels (median 34.3 ng/ml, range 17.6-61) of a control group of 60 healthy non-pregnant women, TM levels were shown to increase throughout pregnancy, median (and range) values being respectively 38.5 (17.6-72.7) from 11 to 20 weeks, 45.2 (22.6-75.2) from 21 to 30 weeks and 54.3 (25.1-114.5) ng/ml from 31st week to delivery. One hour after delivery TM levels were still elevated and dropped three days postpartum to 40.5 (20.9-79.4) ng/ml. The increase of TM levels was correlated with those of tissue-type plasminogen activator and plasminogen activator inhibitor-1 antigens. The large overlap in TM levels between the study periods seems to preclude a clinical use of TM based on reference values from a control group. Our data suggest that it would be more appropriate to take into account TM baseline values in a given woman to examine her TM increase during pregnancy.